2013
DOI: 10.3402/rlt.v21i0.22316
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale innovation and change in UK higher education

Abstract: This paper reflects on challenges universities face as they respond to change. It reviews current theories and models of change management, discusses why universities are particularly difficult environments in which to achieve large scale, lasting change and reports on a recent attempt by the UK JISC to enable a range of UK universities to employ technology to deliver such changes. Key lessons that emerged from these experiences are reviewed covering themes of pervasiveness, unofficial systems, project creep, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…It should be noted here that the latter (Livingstone, 2015) relied solely on an online survey and included personal criticism of the institution with value-laden language. A further case study (Brown, 2013) makes no explicit reference to the methodology used and it was not possible to determine this from a detailed reading of the article.…”
Section: Empirical Studies 2013-2017mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted here that the latter (Livingstone, 2015) relied solely on an online survey and included personal criticism of the institution with value-laden language. A further case study (Brown, 2013) makes no explicit reference to the methodology used and it was not possible to determine this from a detailed reading of the article.…”
Section: Empirical Studies 2013-2017mentioning
confidence: 99%
“…Cluster 3 studies took a holistic multi-stakeholder approach at project-level (Brown, 2013;Garrison & Vaughan, 2013;Stoddart, 2015), faculty or department level (King & Boyatt, 2015;Trevitt, Steed, Du Moulin, & Foley, 2017) or institution-wide, with one focussing on a single institution (Roushan, Holley, & Biggins, 2016) and four taking a multiple-institution approach (Cifuentes & Vanderlinde, 2015;Domingo-Coscollola, Arrazola-Carballo, & Sancho-Gil, 2016;Ng'ambi & Bozalek, 2013;Singh & Hardaker, 2017).…”
Section: Empirical Studies 2013-2017mentioning
confidence: 99%
“…Brown (2013) identifies this approach of cross-team working at the middle management level as being more successful than either top-down or bottom-up approaches in instigating institutional change in technology practice. The staged approach to the policy approval over several months meant that it was considered several times at the committee level and allowed a secure basis for support.…”
Section: Research In Learning Technologymentioning
confidence: 99%
“…It is, therefore, worthwhile to considering briefly how change is accounted for in the higher education sector, and what conceptual perspectives inform change agendas as well as professional development strategies. In a review of models of change management, Brown (2013) identified three approaches to large-scale change in universities: (i) 'top-down' or management driven approaches that are based on predictive outcomes, but may encounter resistance from staff who do not share the vision of change, (ii) 'bottom-up', participatory approaches led by innovative adopters (Rogers, 2003), where there is the risk that adoption is limited, and (iii) distributive leadership approaches, in which change agendas are distributed and managed by participant stakeholders. Brown makes the case for the effectiveness of the distributive leadership approach in large-scale university change projects, despite less predictable outcomes.…”
Section: Accounting For Teaching and Learning Changementioning
confidence: 99%